The Roles of Store Atmosphere in the Consumer Buying Behavior - An’nisa, Vita; H Ahmad, Suryana; Hidayat, Rahmat (International Journal of Engineering and Technology, 2019)
This article presents a store atmosphere created through the exterior, general interior, store layout and interior displays and their influence on consumer buying behavior. The object of this study was Little Wings Café, one of the most-visited cafes in Bandung, Indonesia. This cafe is designed with a library and home theme like a Barbie house. This study employed the quantitative research method using descriptive statistics. A total of 100 samples were collected from a population of 2,310 visitors. The analysis results showed that store atmosphere has a positive influence for buying decision, in which the consumers were mainly attracted by the unique outside design. In addition, the consumers have a high tendency to visit a cafe which can make their mood better and they search for information about cafes prior to visitingÂ